Pembuatan Plang Denah Lokasi Penentuan Daerah Penangkapan Ikan Berbasis Teknologi Bawah Air untuk Masyarakat Teluk Mata Ikan, Nongsa Batam - Muhammad Zainuddin Lubis; Wenang Anurogo; Muhammad Ghazali; Satriya Bayu Aji; Pratiwi Dwi Wulandari; Ganda Surya (Politeknik Negeri Batam, 2022)
This community service begins with the understanding that the Geospatial Information Law No. 4 of 2011 mandates that geospatial information must be disseminated and known to the wider community. On the basis of this geospatial information law, community service activities are carried out for coastal communities and small islands regarding the understanding and skills of the Nongsa community, regarding the determination and mapping of fishing areas (MFA), and chlorophyll maps and depth maps, for approaches to Potential locations in the DPI are important so that coastal communities and small islands recognize the potential and spatial problems on Batam Island. This problem will certainly have an impact on the economy of coastal communities, with it being very difficult to determine the location of fishing, which is the main livelihood for the community. This activity includes the development of science and technology to the community, especially in the use of marine technology that can assist in determining fishing areas which will later help and create independence for coastal communities in Mubut Darat in determining fishing spots or areas in the area. The output of this community service program is increasing the understanding and skills of the community in the Nongsa sub-district, Batam regarding the determination and mapping of fishing areas (MFA), providing planks, making maps of fishing areas and developing teaching materials (textbooks) in Batam City. This activity ran smoothly and provided very new knowledge for the people on the island of Batam-Nongsa.